Maastricht timber-framed construction - remains of a wooden past (Bulletin KNOB, 2004)
This article is about the remains of the medieval timber-framed houses of Maastricht. These wooden houses have gradually disappeared because of the city's fire regulations. Nevertheless, some still remain (partly) and have been investigated in order to give an overview.Research has not yet clarified the early period of timber-framed houses in Maastricht. The only remaining examples date from the beginning of the fifteenth century. By that time the wooden constructions were already in a fully developed stage. The skeleton was placed on a stone cellar and socle and could sometimes even be over 20 meters high. All floors were separately formed out of posts and sill beams which led to a geometric construction of frames. Interties and braces internally supported the frames. The braces could also form a St. Andrews' cross. It has not yet been possible to find a development in the way these braces were applied, because of the small quantity of examples left. However, St. Andrews' crosses seem more popular in the second half of the fifteenth century and the first half of the sixteenth century.The timber-framed houses have a roof that is typical for Maastricht: The ridge is parallel to the street. As houses were 10 to 15 meters deep, the roofs became quite big. From 1612 the city council tried to diminish the wooden buildings in the city, because of the fire risk, but also for more aesthetic reasons. It took several decades for the building regulations to take effect and even in the nineteenth century there were still wooden facades visible in the streets. Now, no wooden facade is left. Only side walls and internal walls remain.In comparison with other cities within the prince-bishopric of Liège, the city council of Maastricht was quite early with their regulations. This can be attributed to the dual government of the city: It was governed by both the prince-bishop of Liège (in whose territory the city was situated) and the Duke of Brabant. The cities of Brabant had started much earlier to banish houses that were completely made of wood. The application of boarding on the timber frames in Maastricht in a certain period can also be attributed to the influence of Brabant as boarding does not occur so much in Liège.Dendrochronological research has been done on eleven buildings which led to some surprising discoveries. The oldest remaining building is a timber-framed wall between Kleine Staat 9 and 11 and dates from 1406 AD. The well-known Dinghuis (Kleine Staat 1) dates from 1473 AD and the most recent dated timber-framed house is Markt 55, dating 1593-1596 AD. Muntstraat 31, believed to be seventeenth century, turns out to be two centuries older: 1455 AD. Because of the small number of remains, it was not possible to construct well-argued theories on the development of the timber-frame constructions. However, the precise dating of the few buildings left, is already a step forward to a better understanding of the timber-frame history of Maastricht.